A visit by John Hejduk to the Almudín of Valencia - Barberá Pastor, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
The research work studies the visit that architect John Hejduk made to the Almudín of the city of Valencia on October 25, 1980 with a group of professors from the School of Architecture. The visit is linked to the conference he gave on the same day about the Masque, a project that will modify the proposals thereafter and he will be developed during the last twenty years of the 20th century. The brief attends the event made by the subject as an essential requirement to understand the ephemeral nature of the Masques. The Masques were projected, interchangeably, for any city. The written analysis conceptualizes the 17th-century Masque as a type of ephemeral architecture that was built inside another building and accompanied by a scenic representation, as a precedent to the 20th-century Masque. The surprise caused to the American architect in the visit to the Valencia building is studied from the possibility he had to influence his later projects. The article analyzes the links and relationships in Valencia, and studies whether the visit could transform the architect. He said: "I did not believe that in a few days you could change your ideas about architecture." The article studies the relations between the professor of the Bronx and the professor of Valencia Cecilio Sánchez-Robles.